Active fillers’ effect on in situ performances of foam bitumen recycled mixtures - Betti, Giacomo; Airey, Gordon; Jenkins, Kim; Marradi, Alessandro; Tebaldi, Gabriele (2016)
Cold recycling is one of the most employed rehabilitation techniques for asphalt pavements and it is becoming more and more important as reducing emissions becomes a priority in the reduction of the greenhouse effect. The main advantages of asphalt cold recycling techniques are the use of reclaimed materials and the fact that there is no need of aggregate heating to make the mixtures. This paper describes the evolution with time of in-situ performances of different foam bitumen-stabilised mixtures made with different active fillers (cement and lime), monitored during the first year from construction. Results are part of a more extensive research programme aimed to investigate the effects of using lime as an active filler in cold-recycled mixtures. Mixtures have been laid down on a specifically designed trial section in Italy, close to Florence. Short-term bearing capacity, immediately after construction, has been evaluated using a light weight deflectometer while to evaluate the mid-term performances falling weight deflectometer (FWD) tests have been performed after 24 hours, 14 days, 28 days and 9 months from construction. During these 9 months the test road was not opened to traffic, so the mixtures experienced almost no traffic (only construction traffic loads). This fact allowed to have the curing process without any influences other than the temperature: it means same curing conditions for all mixtures. Subsequent FWD tests are still ongoing to evaluate the evolution over time of pavement bearing capacity due to traffic. Results obtained positively support the use of lime as an active filler in the foam bitumen-stabilised material and allow to underline the effect of different active fillers in the material behaviour, even if all the mixtures underline excellent performances under traffic loading. FWD tests are scheduled to be repeated every 6 months in order to monitor the stiffness evolution of the mixtures and evaluate the nature of traffic damage.